Environmental Fate, Toxicity, and Mitigation of Per- and Polyfluoroalkyl Substances (PFAS): Advances in Source Reduction and Sustainable Alternatives - Risky Ayu Kristanti; Yan Li; Putri Adia Utari (Tropical Aquatic and Soil Pollution, 2026)
Per- and polyfluoroalkyl substances (PFAS) were widely recognized as emerging environmental pollutants due to their extensive distribution across ecosystems. PFAS were synthetic chemicals composed of alkyl chains bonded to multiple fluorine atoms, and they had been detected in various environmental compartments, including rivers, soil, oceans, and the atmosphere. These compounds originated from a wide range of industrial and consumer products such as textiles, non-stick cookware, aqueous film-forming foams (AFFFs), and cosmetics. Once released into the environment, PFAS persisted for long periods and exhibited toxic effects on both ecosystems and human health. The exceptional stability of PFAS was attributed to the strong carbon–fluorine (C–F) bonds, which were among the strongest in organic chemistry due to fluorine’s high electronegativity. As a result, PFAS were commonly referred to as “forever chemicals” because of their extreme resistance to degradation. Their persistence and bioaccumulative properties had made PFAS contamination a global environmental and public health concern. In response, various source reduction strategies were implemented, including the substitution of PFAS with alternative chemicals, regulatory policies, and increased consumer awareness. In parallel, green chemistry had emerged as a promising approach for developing safer and more sustainable alternatives, such as biopolymers, fluorine-free materials, and short-chain PFAS substitutes. However, further research was still required to improve the performance, safety, and scalability of these alternatives. This study aimed to discuss the sources and environmental impacts of PFAS, evaluate source reduction strategies, and examine green chemistry-based alternatives. It also identified key challenges and outlined future research directions needed to enhance the development and implementation of effective PFAS replacements.